Osteometric assessment of coracoid process of scapula-clinical implications - Kumar V,; Kohli M,; Mehta Vandana,; Suri RK, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
The coracoid process is a bony projection arising from the antero-lateral aspect of the scapula. The variation in the height and length of the coracoid process are responsible for altered size and shape of the space between the coracoacromial arch and the rotator cuff. The study was conducted on sixty-four dry adult human scapulae of unknown age and sex with a view to elucidate the morphological and osteometric details. The length of coracoid process on right side was 41.01±3.55 mm and it was found to be 40.88±3.83 mm on left sided. The breadth of coracoid process was observed as 13.93±1.13 mm and 13.25±1.26 mm on right and left side respectively and the difference between the two sides was statistically significant (p=0.026). Thickness of the coracoid process was 8.59±1.32 mm and 8.01±1.16 mm in right and left sided scapulae. The acromiocoracoid distance was found to be 38.48±4.03 mm on right side and 35.51±3.83 mm on left sided scapulae and the difference between to the two sides showed high statistically significance (p=0.004). Mean coracoglenoid distance was noted 26.23±3.05 mm and 24.94±2.75 mm on right and left sided scapulae respectively. Values of the thickness of coracoid process recorded in the present study are at appreciable variance with the result of previous study. The coracoid process constitutes an important component of the scapular glenoid construct and is involved in many surgical interventions on the glenohumeral joint. Comprehension of standard morphometric details of the coracoid process is vital in traumatic cases, surgical interventions and replacement surgeries in the shoulder region.